2020
DOI: 10.7717/peerj.8904
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression and purification of β-caryophyllene synthase in Nicotiana benthamiana to produce β-caryophyllene in vitro

Abstract: The sesquiterpene β-caryophyllene is an ubiquitous component in many plants that has commercially been used as an aroma in cosmetics and perfumes. Recent studies have shown its potential use as a therapeutic agent and biofuel. Currently, β-caryophyllene is isolated from large amounts of plant material. Molecular farming based on the Nicotiana benthamiana transient expression system may be used for a more sustainable production of β-caryophyllene. In this study, a full-length cDNA of a new duplicated β-caryophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020 ; Muthusamy et al, 2020 ), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020 ; Muthusamy et al, 2020 ), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported sesquiterpenoid production in plants. Artemisia annua beta-caryophyllene synthase was transferred into Agrobacterium through a viral vector in a previous study, and then agroinfiltrated into N. benthamiana leaves to produce 26.5 mg of β-caryophyllene ( Muthusamy et al., 2020 ). Transient co-expression of the parthenolide pathway candidate genes in N. benthamiana was used to reconstitute the co-expression, and up to 1.4 µg of the final product was generated ( Liu et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These include amorpha-4,11-dienesynthase (ADS), epi-cedrol synthase, β-caryophyllene synthase, (E)-farnesene synthase, germacrene A synthase, and squalene synthase. ADS is the only enzyme involved in artemisinin production ( Liu et al., 2011 ; Kanagarajan et al., 2012 ; Cankar et al., 2015 ; Muthusamy et al., 2020 ). Numerous studies have been conducted to increase mono- and sesquiterpene biosynthesis by inhibiting the expression of mono- and sesquiterpene synthase(s) striving for GPPS and FPP using antisense technology or RNA interference ( Li et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and full-length open reading frames of six BnGTR1 and six BnGTR2 paralogs were amplified from genomic DNA and cDNA of cv. Kumily, respectively, using gene specific primers according to published protocols (Kim et al, 2020;Muthusamy et al, 2020), with minor modifications, and confirmed by sequencing. Genomic DNA sequences of different paralogs from the BnGTR1 and BnGTR2 were aligned to find conserved target sites among the paralogs of each gene.…”
Section: Identification and Cloning Of Gtr Genes Sgrna Design And Vec...mentioning
confidence: 99%